Evaluating the Antidiabetic Activity of Aloe niebuhriana Latex in Alloxan-Induced Diabetic Rats and the Development of a Novel Effervescent Granule-Based Delivery System - Bushra Abdulkarim Moharram; Mahmoud Mahyoob Alburyhi; Tareq Al-Maqtari; Abdu Faisal (The Scientific World Journal)
Conclusion: This study highlights the antidiabetic potential of A. niebuhriana latex extract, potentially attributed to its hypolipidemic, hypoglycemic, and α-amylase inhibitory effects. The successful formulation and evaluation of the extract as effervescent granules suggest its potential as an antidiabetic drug.